1994
DOI: 10.1148/radiology.192.1.8208962
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of adrenal masses with MR imaging: comparison of techniques.

Abstract: Although a chemical shift imaging technique and a T2*-weighted sequence helped correctly differentiate among the groups of adrenal masses, the degree of overlap suggests that it is still difficult to evaluate disease in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 0 publications
1
33
0
2
Order By: Relevance
“…Henkelman et al ( 5 ) showed four different T, components for tendon at 2, 8,23, and 56 ms. The first measured data point occurred atsimilar values for the T2 components in tendon and also demonstrated a temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Henkelman et al ( 5 ) showed four different T, components for tendon at 2, 8,23, and 56 ms. The first measured data point occurred atsimilar values for the T2 components in tendon and also demonstrated a temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have suggested other strategies to characterize adrenal masses on cross-sectional images, including evaluation of lesion size, morphologic characteristics, attenuation measurements on precontrast and postcontrast CT scans, and signal intensity (SI) characteristics on postgadolinium MR images (10). Despite these efforts, no generally accepted method has evolved to identify reliably the subset of adrenal adenomas with lower amounts of lipid (11)(12)(13)(14)(15).The purpose of this study was to evaluate the usefulness of the immediate and the 45-second postgadolinium spoiled gradient echo (SGE) MR sequences for differentiation of adrenal adenomas from malignant adrenal tumors. …”
mentioning
confidence: 99%
“…Ichikawa et al [39] berichten über eine Sensitivität von 92% und eine Spezifität von 95% bei Anwendung dieses Kriteriums. Die CSI scheint bisher von allen untersuchten MRT-Techniken am genauesten zu sein (Abbildung 1) [37,[40][41][42].…”
Section: Magnetresonanztomographie (Mrt)unclassified